Posted by **SANDRO!** on Monday, November 6, 2006 at 5:17pm.

Use the Substitution method to solve the system of equations.

y - 2x = -5

3y - x = 5

Solve the first equation for y.

y = 2x-5

Substitute that for y in the second equation and solve for x. Then use the value of x to substitute back into the first equation and solve for y. Post your work if you get stuck.

WOULD IT BE:

4Y-X=0?

y - 2x = -5 (equation 1)

3y - x = 5 (equation 2)

=============

Use equation 1 to solve for y as I did earlier.

y = 2x + 5

Now substitute that value of y (from equation 1) into equation 2.

equation 2 is

3y-x=5. Plug the value for y into this.

3(2x+5)-x=5

Now solve for x. Then use that value for x into equation 1 and solve for y.

Post your work if you get stuck. Not a "would it be" answer.

what is a possible point that lies on the graph

y=-2x-5

yo mama

## Answer This Question

## Related Questions

- How do I do this.?(Math.) - Use the Substitution method to solve the system of ...
- Substitution Method-Plz help - Use the Substitution method to solve the system ...
- Algebra 1 HELP PLZ!!! - Use the Substitution method to solve the system of ...
- subsitution method - Can some one show me how to use the Substitution method to ...
- Substitution Method - Use the Substitution method to solve the system of ...
- substitution method - -x-4y=-14 2x=y+1 Let's look at your two equations. -x - 4y...
- substitution method - -3x+y=-5 x+2y=0 Your equations: -3x + y = -5 x + 2y = 0 ...
- Algebra 1 - What is an equation of a line perpendicular to the line with ...
- Alg-Substitution (check plz) - k well i had to use substitution to find the ...
- algebra - 5x-2y=-5 y-5x=3 substitution Substitute 5x +3 for y in the first ...

More Related Questions